1981
DOI: 10.1002/jmv.1890070102
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes and Virus‐Like Particles Localized in Liver Hepatocytes of Chimpanzees Infected With Non‐A, Non‐B Hepatitis

Abstract: Virus-like particles have been visualized by electron microscopy in the liver hepatocytes of two out of four chimpanzees inoculated with two different human non-A, non-B hepatitis-implicated plasmas. The first two chimpanzees, which were infected with the same inoculum (inoculum A), developed liver histological features characteristic of mild acute viral hepatitis as well as rises in their serum alanine aminotransferase levels. Clusters of intranuclear particles, 22 k 2 nm in diameter, were visualized in one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Several investigators (15)(16)(17) have confirmed the original observation that NANB virus-infected hepatocytes contain cytoplasmic membrane fusions and intranuclear aggregates of 20-to 27-nm particles (18). Direct demonstration of NANB-specified antigen(s) within the nucleii of hepatocytes associated with NANB hepatitis virus-infected liver tissue has also been reported (4,5).…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Several investigators (15)(16)(17) have confirmed the original observation that NANB virus-infected hepatocytes contain cytoplasmic membrane fusions and intranuclear aggregates of 20-to 27-nm particles (18). Direct demonstration of NANB-specified antigen(s) within the nucleii of hepatocytes associated with NANB hepatitis virus-infected liver tissue has also been reported (4,5).…”
Section: Discussionmentioning
confidence: 73%
“…Liver biopsy material was obtained from four chimpanzees (nos. 90, 92, 94, and 159) infected with human plasma containing infectious NANB hepatitis virus (16). Liver wedge biopsies were obtained from each of the animals at a time during which liver enzyme profiles were elevated and pathological indicators of viral hepatitis were noted (16).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations